USE OF DIGITAL TECHNOLOGIES AND DIGITIZATION TOOLS IN THE CONTEXT OF MANAGEMENT OF KEY BUSINESS PROCESSES OF MANUFACTURING ENTERPRISES IN UKRAINE - PLOTNIKOV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This scientific article examines the theoretical, methodological and applied principles of digital transformation of Ukrainian processing enterprises in the context of the development of the digital economy. The author proves that digitalization is a key factor in increasing the efficiency of management, flexibility and sustainability of production systems. Based on statistical data, an analysis of the dynamics of digital integration of enterprises in the industrial sector for 2018–2024 was carried out, which showed a gradual increase in the proportion of enterprises with access to the Internet and an increase in the digital involvement of personnel. A positive trend in the use of social media, websites and cloud computing was identified, however, uneven rates of implementation of innovative technologies were established. An empirical study was conducted on the example of the enterprises PAP «Agroprodservice», LLC «K-Agroinvest Trade», PrJSC «Ternopil Dairy», PrJSC «TerA» and PrJSC «Opillya Brewery», which confirmed the differentiated nature of digitalization in terms of the level of technological maturity, scale of application and functional coverage of business processes. It was determined that the highest level of digital integration is demonstrated by enterprises that have implemented comprehensive ERP, CRM, MES and SCM systems, AI and Big Data technologies. The key problems of digitalization are outlined – limited funding, a shortage of digital competencies, fragmentation of IT infrastructure, insufficient level of cybersecurity and uneven development of regional digital infrastructure. Directions for increasing the efficiency of digital transformation are proposed, in particular, expanding state support for innovations, training personnel with IT competencies, strengthening business cooperation with technological partners, and implementing unified standards for digital interaction in supply chains. It is noted that the further integration of digital technologies into the business processes of processing enterprises is of strategic importance for increasing their competitiveness, innovative capacity, and sustainable development in the conditions of the digital economy of Ukraine. further integration of digital technologies into the business processes of processing enterprises is of strategic importance for increasing their competitiveness, innovative capacity, and sustainable development in the conditions of the digital economy of Ukraine. The results of the study have practical significance for the formation of strategies for managing digital changes, increasing the competitiveness and sustainable development of processing enterprises in Ukraine.